User Satisfaction Analysis of the Muslim Pro Application using PIECES Method - anjani, sri; Megawati, Megawati; M.Afdal, M.Afdal; Rahmawita, Medyantiwi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
User satisfaction serves as a benchmark for applications and helps developers improve the quality of future applications. Muslim Pro is an application that provides various services for Muslims. This app is designed to assist Muslims in performing their religious duties more easily and systematically. Numerous negative user reviews about Muslim Pro indicate that user satisfaction regarding the company's performance is still low. The aim of this research is to determine the level of satisfaction with the Muslim Pro application based on user experience. To measure user satisfaction, this study employs the PIECES method, which consists of Performance, Information, Economic, Control, Efficiency, and Service. Data collection was conducted by distributing a questionnaire to 100 active students at UIN Suska Riau who use the Muslim Pro application. The results for each variable received the following average scores: the Performance variable scored 4.38, indicating satisfaction; the Information variable scored 4.27, indicating satisfaction; the Economic variable scored 4.26, indicating satisfaction; the Control variable scored 3.97, indicating satisfaction; the Efficiency variable scored 4.24, indicating satisfaction; and the Service variable scored 4.41, indicating satisfaction. Therefore, the overall average user satisfaction score is 4.25, which indicates a satisfactory level of service provided by Muslim Pro, categorizing it as